EVALUATION OF DYNAMIC BALANCE IN WOMEN ACCORDING TO SOME ANTHROPOMETRIC VARIABLES (Journal of Pharmaceutical Negative Results, 2022)
The aim of the study is to examine the dynamic balance order in women in the context of age, height, body weight, body mass index (BMI), leg length, waist and hip circumference measurement values. Thirty-five female volunteers with a mean age of 39.03 ± 7.51 years were included in the study. Participants' ages, heights, body weights, BMI, leg lengths, waist and hip circumference values were determined. Again, the balance values reached on the Anteroposterior (AP) axis and the balance values reached on the Horizontal axis (ML) were determined, including the right, left and double feet of the participants. In the analysis of the data obtained, descriptive and anova tests were used in the SPSS 22 package program. Among the dynamic balance types, it was determined that only the bilateral AP balance level of the participants differed significantly according to the age variable (p= 0.015) and the right foot AP balance level differed significantly according to the body weight (p= 0.030). It was revealed that the balance types in question did not differ significantly (p<0.05) in all other anthropometric characteristics evaluated. As a result, it was determined that the left foot AP and ML balance values in the variables included in the study were at the level of normal or ideal balance values. On the other hand, the AP and ML balance values of the right foot were generally found to be at the level of weak balance values.